(untitled) (Research, Society and Development, 2020)
Objectives: To present a tool developed to actively search for suspected tuberculosis cases; to describe the steps for its construction; and to assess the applicability and functionality of the instrument. Methodology: This is a qualitative descriptive field research carried out from May 2018 to May 2020; whose data was collected through a questionnaire with semi-structured questions. The research participants were 25 students from a technical nursing course. Results: Statistical process control was applied to analyze the questionnaire. There was an evolution in the average number of students, which went from 5.0 to 8.2 points. As the control limits are quite far from the mean, it can be said that there is a dispersion among the students’ knowledge, this being a factor that persisted after the training: standard deviation before 1.6 and standard deviation after 1.3. It was found that 96% (22) of students had no problem installing the web application. Only 4% (one) scored “yes” for this question. All participating students, 100%, considered the application easy to understand, as well as admitted that there was no difficulty in entering the information in TB – Active Search. Conclusion: It is believed that the application entitled TB – Active Search can assist in the prevention and capture of new cases of tuberculosis within the territory. The incorporation of this new technology for the Community Health Agent is also expected. It is necessary to change, innovate and advance on issues related to the prevention of tuberculosis so that changes can be made in relation to the national scenario in a sustainable manner.